Petrography, geochemistry and geochronology of San Jorge porphyry Cu-Au deposit, Mendoza, Argentina: Constraints for the timing of magmatism and associated mineralization - Garrido, Mirta Mabel (2018)
The San Jorge porphyry Cu-Au deposit, Argentina, integrates the Paleozoic to Early Jurassic metallogenic belt recognized in the Southern Andes. San Jorge is currently the only deposit considered economically viable due to its supergene enrichment. Previous studies have reported Middle to Upper Permian ages (257-270 Ma) for the intrusion-mineralization processes. Granite porphyry, two granodiorite porphyries (G1 and G2) and an alkali-feldspar granite dike were recognized. These granites intrude sedimentary rocks (Yalguaráz Formation) that hosts the main mineralization. Two tourmaline alteration events occurred prior to thepotassic episode. They are overprinted by phyllic alteration that has an elongated shape with potassic mineralized cores. The mineralization is linked to the potassic alteration in the sedimentarysequence and in the granite porphyry that has the highest Cu contents (1% to 3%). The phyllic alteration has pyrrhotite, arsenopyrite and minor chalcopyrite. Digenite, chalcocite and covellite appear in the supergene; malachite and brochantite in the oxide; and goethite, hematite and jarosite in gossan zones. The granitic porphyry, granodiorite porphyries G1 and two potassic alteration biotites are of Early Permian age. This event produces the potassic alteration and mineralization and is 15 Ma older than the ages determined by other authors. The granodiorite porphyry G2 and the alkali feldspar granite dike are Upper Permian in age. The results suggest that the evolution of the western margin of Gondwana began in late Carboniferous and continued during the Permian period. In this Paleozoic to early Jurassic metallogenic belt, La Voluntad Cu-Mo porphyry is the oldest deposit (early Pennsylvanian, Garrido et al. 2008). Mineralized and no mineralized San Jorge granites (Early Permian-Late Permian) integrate the intrusive event of the Choiyoi Group.